2009
DOI: 10.1111/j.1467-6419.2009.00578.x
|View full text |Cite
|
Sign up to set email alerts
|

The Economics of Networks: A Survey of the Empirical Literature

Abstract: Network effects, the increase in value of consuming a product if many other consumers use the same product, are a feature of many markets and in particular of many high-technology products. This paper surveys the burgeoning empirical literature that has developed especially during the last years. After theoretical work dominated the earlier years of research in this area, newer research has combined theoretical models with empirical studies and applied work with direct implications for public policy, marketing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(18 citation statements)
references
References 72 publications
2
16
0
Order By: Relevance
“…Noticeably, the Bosnia market dynamics rely on a different set of pertinent issues, to some extent confirming the findings of Grajek (2010) as well as Sobolewski and Czajkowsi (2012). Also, our findings have confirmed the importance of social ties like family or friends in carrier selection rather than the overall size of the operator or price (Karacuka et al, 2013), and clearly show that social networks, compared to price or the installed base, have more significant influence on operator choice, confirming the findings of Birke (2009) and Basaran et al (2014).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Noticeably, the Bosnia market dynamics rely on a different set of pertinent issues, to some extent confirming the findings of Grajek (2010) as well as Sobolewski and Czajkowsi (2012). Also, our findings have confirmed the importance of social ties like family or friends in carrier selection rather than the overall size of the operator or price (Karacuka et al, 2013), and clearly show that social networks, compared to price or the installed base, have more significant influence on operator choice, confirming the findings of Birke (2009) and Basaran et al (2014).…”
Section: Discussionsupporting
confidence: 85%
“…In other words, a newcomer to the market will not be able to estimate all effects of its entry, which could result in an increase in average cost and ultimately increase in prices for consumers. Also, one of the key characteristics of network industries is the existence of network effects whereas the greater the number of people are using product or service it becomes more valuable for all the consumer using it (Rohlfs, 1974;Katz and Shapiro, 1994;Arthur, 1990Arthur, , 1996Economides, 1996;Birke, 2009). Often, the success of certain products/services in network industries cannot be attributed to superior technology or better solutions, but to compatibility with other products and/or the overall size of their networks.…”
Section: Introductionmentioning
confidence: 99%
“…We can also compare the results in the current research with the literature on product standards, which has demonstrated that competition can result in the adoption or preservation of socially inefficient standards (see, e.g., Bessen and Farrell 1994; Farrell and Saloner 1985, 1986; Katz and Shapiro 1985, 1994). Although the body of theoretical work is now extensive, there has been recent recognition that more empirical work on this topic is needed (Birke 2009; Suarez 2005). Much of the literature stream has focused on the role of network effects in technology markets (see, e.g., Basu, Mazumdar, and Raj 2003; Dubé, Hitsch, and Chintagunta 2010; Gupta, Jain, and Sawhney 1999; Sun, Xie, and Cao 2004; Wang and Xie 2011).…”
Section: Related Literaturementioning
confidence: 99%
“…A large empirical literature has supported the important role of social influences in explaining individual choices regarding a variety of economic, social and health behaviours (see Brock and Durlauf (2001) and Birke (2009) for a survey). In what follows, we use the terms social interaction, network effects and peer or social influences as synonymous, to indicate what has been referred to by Manski (1993) as an endogenous effect.…”
Section: Introductionmentioning
confidence: 99%